LORY PLATEAU GROUND WATER FLOW DISTRIBUTION: (on the data of geophysical investigations) (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
Analysis of geophysical investigations data brought about new data concerning ground water flow distribution of Lory plateau. Compiled geological-geophysical cross-sections and resultive map of regional confining strata shows the existence of highly dissected network of buried valleys. Ground water recharge area is located at Jawakhet Ridge which is the basic area of ground water cumulative runoff development. One of mentioned directions of ground water flow is well-known Tashir interlava flow. The most water-bearing area is located in its central part, where have been incountered a number of ground water horizons.
Keywords: Lory plateau; Jawakhet Ridge; Tashir interlava flow